Propanolol: An option when treating infantil haemangioma. Clinical case. - Alves, Sandra (2014)
Infantile haemangioma, a benign vascular tumour, is the most frequent non malignant neoplasm in children. Although spontaneous regression occurs in most cases, in about 10% of patients medical or surgical treatment is warranted due to its localization, volume or associated complications. The authors present a case report of a 4 year old child with an infantile haemangioma of the upper lip, previously treated with systemic corticosteroids and PDL Laser, and then was submitted to medical treatment with propanolol. Propanolol, a β-blocker, is an effective and safe option for the treatment of infantile haemangioma with aesthetic implications and/or other complications. Although its clinical use is not definitely accepted for this purpose, the excellent results obtained in the last several years have transformed this molecule into the first line of treatment in infantile haemangioma, replacing the use of systemic corticosteroids.